Estrategias de merchandising en la Ferretería Jb de la ciudad de Babahoyo. - Vera Rivera, Jaira Alejandra (2023)
The present case study has as its theme: "MERCHANDISING STRATEGIES IN THE JB SHOP IN THE CITY OF BABAHOYO", whose purpose is that the company focuses on positioning itself in the market to generate profitability by efficiently using its sales strategies and technologies through the internet and social networks. The relevance of merchandising within a company contributes to increase profitability, attract potential customers and improve the relationship between employees. This marketing method adjusts to the constant changes in technology, society and economy, which are inherent to the market. In the same way, it allows finding ways to satisfy customer needs and, at the same time, to be competitive in the market, while optimizing resources and generating profitability for the company. The objective of this case study is to implement a marketing strategy to increase sales in Ferreter JB, for this it will be essential to conduct research on different theoretical bases related to marketing, to identify and differentiate which marketing strategy is more effective taking into account the tastes or preferences of the citizens of Babahoyo and its surroundings are suitable to increase sales of the company in the local market. In this sense, the research leads to analyze the situation of the hardware store from the perspective of trade, seeking to create virtuous circles, which is ultimately to increase sales and reduce costs, which in turn generates benefits for the businessman and the customer, since the first gets profits for the profitability of the business and the second for the quality of service and product.